Finding Inner Peace: An Exploration of Forgiveness Therapy for Bullying Trauma Recovery - Yandri, Hengki; Kholidin, Farid Imam; Sujadi, Eko; Juliawati, Dosi (Program Studi Bimbingan dan Konseling Islam, 2024)
This study aims to explore the effectiveness of Forgiveness Therapy in reducing the emotional pain of bullying in college students. This case study involved client